One year failure rate for de-novo ventriculo-peritoneal shunts in children from a small volume paediatric neurosurgical unit. (August 2013) - Lang, J.; Amato-Watkins, A.; Amarasinghe, S.; Goetz, P.; Bukhari, S.; Leach, P.
Abstract: It is the belief of some that results of shunt surgery for the treatment of hydrocephalus in children are improved if the surgery is performed in high-volume centres. Currently in the UK paediatric neurosurgery is undergoing a service review. As part of this review a set of standards of care are being drafted which state that 1-year failure rates and infection rates for de-novo ventriculo-peritoneal shunts in children should be less than 40% and 10%, respectively. Our de-novo shunt infection rate (4.3%) and our 1-year failure rate (28.6%) are well within the standards set by this process and comparable to published literature from much higher volume centres.